2021
DOI: 10.1111/jace.18225
|View full text |Cite
|
Sign up to set email alerts
|

Preparations of lanthanum hexaboride (LaB6) and cerium hexaboride (CeB6)

Abstract: Due to strong anti-poisoning ability, good emission stability, high emission current density, lanthanum hexaboride (LaB 6 ) and cerium hexaboride (CeB 6 ) have been maturely applied in electron emission emitter. In this paper, a new manufacturing method for LaB 6 (or CeB 6 ) powder was proposed by using La 2 O 3 (or CeO 2 ), B 4 C, and Al as raw materials. After high-temperature reaction in the range of 1673-1773 K and the following alkaline leaching at 90 • C, LaB 6 or CeB 6 powder with particle size of about… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…In 1951, Lafferty identified that LaB 6 possesses excellent hot electron emission properties [1]. Since then, rare earth hexaborides have attracted significant attention from researchers [2,3]. LaB 6 is regarded as an ideal material for electron-emitting cathodes owing to its low work function, high mechanical strength, and chemical stability [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…In 1951, Lafferty identified that LaB 6 possesses excellent hot electron emission properties [1]. Since then, rare earth hexaborides have attracted significant attention from researchers [2,3]. LaB 6 is regarded as an ideal material for electron-emitting cathodes owing to its low work function, high mechanical strength, and chemical stability [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%